Positive steady states of the Holling–Tanner prey–predator model with diffusion - Peng, Rui; Wang, Mingxin (Proceedings of the Royal Society of Edinburgh. Section A. Mathematics, 2005)
This paper is concerned with the Holling–Tanner prey–predator model with diffusion subject to the homogeneous Neumann boundary condition. We obtain the existence and non-existence of positive non-constant steady states.